THE HISTORY OF THE MATHEMATICS INTO DIDACTIC SEQUENCES IN THE TEACHERS' INITIAL FORMATION - Moura, Elmha Coelho Martins (2019)
This paper presents results of a case study accomplished in the discipline of Practice of Teaching of Mathematics, of the course of Mathematics of the Federal University of Integration of Latino America (UNILA). Ponte (1994) affirms that a case study is an empiric investigation whose results are presented, most of the time, in descriptive form. However, it can has an analytical form if it interrogates a situation and to confront it with other known situation. The case study presented in this paper is a qualitative research. In it we analyzed contributions of the history of the mathematics and history of mathematics education for the teachers' initial formation. The data was collected with interview, audios of dialogues concerning the activities among the professor and student, the student's notebook, a video-class produced by him, and professor’s annotations. This study of case shows that the history can contribute to the construction of mathematical concepts and for the reflection about mathematics teaching and bring news results when it is confronted to others researches that was made by members of our research group.